Coping Strategies Predictive of Adverse Outcomes among Community Adults. Issue 12 (29th April 2013) - Woodhead, Erin L.; Cronkite, Ruth C.; Moos, Rudolf H.; Timko, Christine
<x xml:space="preserve">Abstract</x> Objectives To examine associations between coping strategies at baseline and adverse outcomes 13 years later, and whether gender and age moderated these associations. Method Participants (N = 651) completed a survey on demographic characteristics, coping strategies, and psychosocial outcomes (negative life events, alcohol consumption, drinking problems, and suicidal ideation). Results At the follow‐up (N = 521), more use of avoidance coping was associated with more drinking problems and suicidal ideation at follow‐up. Men high in avoidance coping reported more alcohol consumption and suicidal ideation at follow‐up than did men low on avoidance coping. Younger adults high in avoidance coping reported more negative life events at follow‐up than did younger adults low on avoidance coping. Conclusions Reliance on avoidance coping may be especially problematic among men and younger adults.